2019
DOI: 10.1155/2019/6824543
|View full text |Cite
|
Sign up to set email alerts
|

Study of Shear Capacity of Jointed Rock Mass with Prestressed Anchor Bolt

Abstract: Rock mass failure caused by jointed plane is the common disaster in geotechnical engineering. Research on shearing property of jointed rock mass with prestressed anchor bolt and its mechanical property is an aspect for the stability analysis of rock slope and tunnel. This paper studies the stress and deformation of bolt and jointed plane, as well as anchored body and rock mass during shearing by indoor model testing and theoretical analysis. The shearing strength and mechanical property of anchored jointed pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…From the test results, the bolt-grout interface exhibits different failure modes with different rib spacing, normal stress and rib angle [34]. The study of interfacial shear failure characteristics is crucial for analyzing the shear failure mechanism of the bolt-grout interface, and then analyzing the shear mechanical properties of the rock bolting system [40]. The normal displacement-shear displacement curves under different rib angle conditions have roughly the same morphology, and the normal displacements show a tendency to decrease and then increase and then level off, as shown in Figure 12.…”
Section: Interface Shear Failure Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the test results, the bolt-grout interface exhibits different failure modes with different rib spacing, normal stress and rib angle [34]. The study of interfacial shear failure characteristics is crucial for analyzing the shear failure mechanism of the bolt-grout interface, and then analyzing the shear mechanical properties of the rock bolting system [40]. The normal displacement-shear displacement curves under different rib angle conditions have roughly the same morphology, and the normal displacements show a tendency to decrease and then increase and then level off, as shown in Figure 12.…”
Section: Interface Shear Failure Characteristicsmentioning
confidence: 99%
“…From the test results, the Bolt-Grout interface exhibits different failure modes with different rib spacing, normal stress and rib angle [34]. The study of interfacial shear failure characteristics is crucial for analyzing the shear failure mechanism of the Bolt-Grout interface, and then analyzing the shear mechanical properties of the rock bolting system [40].…”
Section: Interface Shear Failure Characteristicsmentioning
confidence: 99%
“…Based on the bolt-rock interaction model, Zhao et al [22] derived a theoretical solution for the internal force of anchor bolts, and then proposed an anchor-rock interaction model of the fully grouted anchor bolts. By utilizing laboratory tests and theoretical analysis, Zhao et al [23] investigated the deformation and axial force of rock bolts, anchored bodies, and rock mass under shear action. Taking the Muzhailing tunnel as the research context, the mechanical responses of anchor plates with different shapes and sizes have been systematically explored in squeezing large-deformation tunnels [24].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that concrete does not crack around the anchor plate as long as the prestressing force is less than 50% of the elastic limit of the anchor rod. Similarly, Zhao et al [29] conducted experimental studies on prestressed anchor rods embedded in rock and successfully demonstrated that prestressing plays an important role in shear strength. Based on a nonlinear finite element model of the column base, Razzaghi & Khoshbakht [30] conducted a study to examine the connection behaviour and identify the effects of different components, such as the base plate, anchor rods, and stiffeners.…”
Section: Introductionmentioning
confidence: 99%